The hemostatic properties of thawed pooled cryoprecipitate up to 72 hours. Issue 6 (28th March 2016) - Green, Laura; Backholer, Lucy; Wiltshire, Mike; Platton, Sean; Stanworth, Simon J.; Cardigan, Rebecca
Abstract : BACKGROUND: There is increasing interest in replacing fibrinogen early for the treatment of major hemorrhage. In countries where cryoprecipitate is the main concentrated source of fibrinogen, the thawing process complicates the timely availability of cryoprecipitate for transfusion early during major bleeding. The aim of the study was to investigate the hemostatic quality of cryoprecipitate, thawed and held at 18 to 24°C for up to 72 hours. STUDY DESIGN AND METHODS: Pooled cryoprecipitate (16 units [eight group O and eight group A]) were thawed at 35 ± 2°C for 20 minutes and held at ambient temperature (18‐24°C) for up to 72 hours. Samples were tested at 0, 4, 10, 24, 48, and 72 hours after thawing for Factor (F)VIII, fibrinogen activity, FXIII, rotational thromboelastometry (ROTEM), and thrombin generation (TG). RESULTS: There were no significant changes in levels of fibrinogen and FXIII over 72 hours. There was a significant decrease (p < 0.001) in FVIII at 24, 48, and 72 hours compared with the baseline; however, at all time points units met the UK specification for FVIII level. The peak thrombin, endogenous thrombin potential, and all ROTEM variables remained unchanged after 72 hours. CONCLUSIONS: The hemostatic properties of thawed pooled cryoprecipitate, maintained at ambient temperature, remain stable for up to 72 hours. Stocking a prethawed product may optimize inventory management, to ensure product availability for rapid transfusion. Further studies need to assess the potential risk of bacterial contamination arising from storage at ambient temperature to determine the maximum shelf life for cryoprecipitate after thawing.